2019
DOI: 10.1177/0971521518811174
|View full text |Cite
|
Sign up to set email alerts
|

Does Menstrual Hygiene Management in Urban Slums Need a Different Lens? Challenges Faced by Women and Girls in Jaipur and Delhi

Abstract: For the first time since Independence, India’s urban population has registered a higher increase than the rural population. Increasing urbanbiased economic activity and job creation are leading to rapid urbanisation, and a greater number of poor people today are living in cities and towns in India. Slums, often the residence of migrants and urban poor, are underserved areas with poor housing, insufficient living space, basic infrastructure and services such as clean drinking water, drainage and electricity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Lack of knowledge, embarrassment and social taboos affect adolescent girls. Menstrual hygiene practices are influenced by cultural and religious beliefs, parental influence, economic status and socioeconomic pressures and these often act as barriers to good hygiene (Chakravarthy et al, 2019; Kaur et al, 2018; Mishra & Prakash, 2019). We observed that low literacy rates and lower awareness were associated with taboos and restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of knowledge, embarrassment and social taboos affect adolescent girls. Menstrual hygiene practices are influenced by cultural and religious beliefs, parental influence, economic status and socioeconomic pressures and these often act as barriers to good hygiene (Chakravarthy et al, 2019; Kaur et al, 2018; Mishra & Prakash, 2019). We observed that low literacy rates and lower awareness were associated with taboos and restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Where the physical state of WASH infrastructure was mentioned, it related to the quantity of available and physically functional toilets/latrines [22,26,28,32,33,37,40,44,46,58,63,73,75,76,78,81,86,87,89,91], the design of toilets/latrines [32,37,40,44,48,51,57,63,64,68,71,73,75,81,83,87,90,97], the quality and availability of running water in and around toilets or latrines [18,20,31,33,37,39,40,45,46,48,49,…”
Section: Reasoning Behind Behaviourmentioning
confidence: 99%
“…availability of soap for washing [20,33,49,53,54,[56][57][58]60,61,63,64,66,67,73,77,90,91] and the availability of a physically functional disposal mechanism and/or service for used material [18,28,[31][32][33][34][35][36][37]42,[44][45][46][47][48]52,53,57,58,60,62,63,[66][67][68]71,76,77,82,83,86,90,91,…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations